Project Report on Design and Fabrication of Dynamic Balancing Machine - SHANMUGAM G M, CANNANE D, SHANKAR K P, ILAGOVAN V, and RAMESH (1993)
INTERNAL GUIDE: PRASAD REDDY B R, MVJCE
Keywords: Dynamic Balancing Machine